Gesture Visualization from Babad Diponegoro (UNESCO’s MoW) into Digital Character using Motion Capture - Harry Nuriman; Setiawan Sabana; Intan Rizky Mutiaz; Rikrik Kusmara Andryanto (International Journal of Science and Society, 2021)
The image of Prince Diponegoro as a national hero of Indonesia is very strong. However, there are controversies and myths regarding his characterization. The researcher deconstructs the character of Prince Diponegoro by appropriating Raden Saleh's painting entitled Penangkapan Pangeran Diponegoro by tracing the authentic script from the autobiography of Babad Diponegoro. The manuscript is examined using an intertextuality approach. Prince Diponegoro is constructed based on the physical characteristics contained in the Babad Diponegoro text into a three-dimensional digital model. The results are then rearranged using the deconstruction method by detaching from the existing stereotype of Prince Diponegoro and displaying his character and habits as written in Babad Diponegoro. A number of questions to be answered through this research are what can be visualized from the character of Prince Diponegoro using a textual approach, especially based on Babad Diponegoro, why does the character and identity based on Babad Diponegoro need to be visualized and what methods can be used to bring out the body and character. through the use of digital technology which includes embodiment, motion, gesture, sound, light, interactivity so as to provide a new experience for the audience. The result was a series of movements and visuals that enriched the characterization of Prince Diponegoro. All characters, both those that have been formed for a long time and those that were only known after the translation of Babad Diponegoro, were shown in the virtual experiment entitled Hikayat Dipanegara. The results showed that appropriation using different dimensions and technology resulted in a new image of Prince Diponegoro. The crossing of signs that occurs between real and virtual experiences and in the context of time can provide a new experience which may change the perspective or understanding of things.